2018
DOI: 10.3390/cosmetics5010009
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Ubiad1 for Epidermal Keratinocytes Involves More Than CoQ10 Synthesis: Implications for Skin Aging

Abstract: Abstract:The significance of Coenzyme Q10 (CoQ10) as an anti-oxidant barrier of the skin, as well as a key component in anti-aging strategies for skin care products, has been firmly established. Biosynthesis of CoQ10 in the mitochondria is well known, but there is only limited information on the non-mitochondrial synthesis of CoQ10 in the skin. Recent findings in zebrafish identified that a tumor suppressor, Ubiad1, is also a key enzyme in the non-mitochondrial synthesis of CoQ10. The purpose of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
0
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
1
0
0
4
Order By: Relevance
“…In line with previous studies [ 22 , 50 , 51 ], we then showed that UBIAD1 KD -dependent depletion of plasma membrane CoQ10 blocks cell proliferation and triggers ROS increase, lipid peroxidation and apoptotic cell death in melanoma cells. Importantly, redox lipid balance, DNA damage and viability of UBIAD1 KD cells were rescued by restoring the antioxidant potential of plasma membranes through idebenone treatment.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies [ 22 , 50 , 51 ], we then showed that UBIAD1 KD -dependent depletion of plasma membrane CoQ10 blocks cell proliferation and triggers ROS increase, lipid peroxidation and apoptotic cell death in melanoma cells. Importantly, redox lipid balance, DNA damage and viability of UBIAD1 KD cells were rescued by restoring the antioxidant potential of plasma membranes through idebenone treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Kulit dapat mencerminkan kondisi tubuh serta sebagai penunjang penampilan dari seseorang. Umumnya kondisi fisik yang kurang sehat ditunjukkan dengan tampilan kulit yang kusam, tidak elastis dan berkerut (Barel et al, 2014;Labarrade et al, 2018). Sejalan dengan adanya keinginan untuk menjaga penampilan dan meminimalkan kekurangan tersebut, minat pasaran terkait kosmetika semakin berkembang (López-Alarcón & Denicola, 2013;Omeroglu et al, 2012).…”
Section: Pendahuluanunclassified
“…Secara umum, proses aging dapat disebabkan karena faktor intrinsik yang terjadi karena genetik atau warisan bahkan pengaruh usia, dan faktor ekstrinsik akibat pajanan dari asap rokok, polusi, dan paparan sinar UV secara berlebih. Dianatara pajanan tersebut, paparan sinar matahari paling berkontribusi dalam hal penuaan secara ekstrinsik sehingga disebut sebagai photoaging (Loo et al, 2012;Rowe & Sheskey, 2009).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations